1983
DOI: 10.1111/j.1365-2265.1983.tb02978.x
|View full text |Cite
|
Sign up to set email alerts
|

Fertility After Childbirth: Pregnancy Associated With Breast Feeding

Abstract: During studies on the resumption of fertility postpartum in 12 breast feeding mothers who were using no contraception, eight pregnancies occurred. In seven cases these pregnancies occurred while the mothers continued to breast feed while in one it occurred within 2 weeks of weaning. In two cases pregnancy occurred prior to first postpartum menstruation but followed an abrupt decline in suckling frequency and duration resulting in resumption of follicular development and ovulation. In the remaining six cases, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
3

Year Published

1988
1988
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 8 publications
0
29
0
3
Order By: Relevance
“…anorexia nervosa; Katz & Vollenhoven 2000) whereas over-nutrition and obesity are generally associated with impaired folliculogenesis, reduced oocyte quality and embryonic failure (Crosignani et al 1994, Norman & Clark 1998, Bellver et al 2003. Further, the duration and severity of post-partum anovulation is directly associated with the nutritional status of the mother and the amount of nutritional supplementation (milk) provided to the suckling young (McNeilly et al 1983, Butler & Smith 1989. Finally, nutrition profoundly affects the presentation and natural history of polycystic ovary syndrome, which is known to affect 5 -10% of women of reproductive age and is the most common cause of anovulatory infertility (Franks 1995).…”
Section: Introductionmentioning
confidence: 99%
“…anorexia nervosa; Katz & Vollenhoven 2000) whereas over-nutrition and obesity are generally associated with impaired folliculogenesis, reduced oocyte quality and embryonic failure (Crosignani et al 1994, Norman & Clark 1998, Bellver et al 2003. Further, the duration and severity of post-partum anovulation is directly associated with the nutritional status of the mother and the amount of nutritional supplementation (milk) provided to the suckling young (McNeilly et al 1983, Butler & Smith 1989. Finally, nutrition profoundly affects the presentation and natural history of polycystic ovary syndrome, which is known to affect 5 -10% of women of reproductive age and is the most common cause of anovulatory infertility (Franks 1995).…”
Section: Introductionmentioning
confidence: 99%
“…32,33 Among Scottish women, it has been observed that ovulation does not occur while the infant is being breastfed for at least six times for a total of 65 minutes distributed in 24 hours. 34 However, other studies have not confirmed this finding, and they have suggested that there is not a minimal number of feedings that guarantees the ovulation interval. 35 Once any other kind of liquid is introduced in the infant s diet, the infant tends to suck less because his hunger and thirst are partially appeased by these liquids.…”
Section: Lactational Amenorrheamentioning
confidence: 47%
“…[23][24][25][26][27] Many studies have presented the relationship between breastfeeding and postnatal amenorrhea, and the occurrence of a consequent longer intergestational period. 10,[28][29][30][31][32][33][34][35][36][37][38][39][40][41] Other benefits for lactating women are the faster loss of weight gained during the pregnancy, [38][39][40][42][43][44][45] and the reduced postnatal uterine bleeding, which leads to less anemia 10 due to the faster uterus involution caused by the greater oxytocin release. 46 If compared to the advance of the knowledge about the role played by breastfeeding and the human milk in the infants health, the knowledge about the benefits of breastfeeding for women is scarce, and, therefore, this topic must be further investigated in the next decades.…”
Section: Introductionmentioning
confidence: 99%
“…14,16,17 Lactational amenorrhea can be used as an effective method of contraception provided the woman is exclusively breastfeeding (on demand, day and night more than 5 times per day, total suckling duration greater than 65 minutes, and at least 10 minutes per feed), 35 has not resumed menses and is within six months of delivery. 16,23,27 This method, when used properly, is at least 98% effective during the first 6 months postpartum.…”
Section: Lactational Amenorrhea Methodsmentioning
confidence: 99%